#### Answer

y-6=-4(x+1)
y=-4x+2

#### Work Step by Step

y-y$_1$=m(x-x$_1$)
y-6=-4(x-(-1))
y-6=-4(x+1)
This is point slope form. Isolate y to find slope-intercept form.
y-6=-4(x)-4(1)
y-6=-4x-4
y-6+6=-4x-4+6
y=-4x+2
This is slope-intercept form.

Published by
Pearson

ISBN 10:
0-13417-805-X

ISBN 13:
978-0-13417-805-9

y-6=-4(x+1)
y=-4x+2

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.